The Influence of Individual Counseling Services with REBT Approach to Overcome Social Anxiety in Adolescents at SMPIT Al-Ulum Medan - Maritza, Safrina Dita; Siregar, Alfin (UIN Sultan Aji Muhammad Idris Samarinda, 2024)
The aim of this research is to measure the effect of individual counseling services Rational Emotive Behavior Therapy (REBT) to overcome adolescent social anxiety at SMP Islam A-Ulum Terpadu Medan. The type of research used is quasi-experiment. The number of samples used was 10 students who entered the experimental class and control class. The sample used is a non-probability sampling sample using purposive sampling technique. Data collection used social anxiety psychological scale. Data analysis was carried out using the t-test. This analysis method is to measure the average value of the control class and the experimental class. Based on the paired sample t-Test test, it shows that the pair 1 output in the control class obtained a tcount value of 3.604 with a Sig value. (2-tailed) of 0.023> 0.005, meaning Ho is accepted and Ha is rejected. While the pair 2 output in the experimental class obtained a tcount value of 15.235 with a Sig value. (2-tailed) of 0.000 <0.005, it means that Ha is accepted and Ho is rejected. This shows that the experimental class using individual counseling services with the Rational Emotive Behavior Therapy (REBT) approach is effective for overcoming adolescent social anxiety at Al-Ulum Integrated Islamic Junior High School Medan